(untitled) (Global Journal of Management and Business Research, 2023)
This article delves into the enormous effect that entrepreneurial spirit has on modern company strategy. This article provides an in-depth look at some of the most important facets of entrepreneurship, including its origins, disruptive nature, technology developments, customer-centric approaches, collaborative ecosystems, risk management, scaling, and lessons from successful entrepreneurs. Entrepreneurship has reshaped the way businesses operate by stimulating innovation, testing the status quo of established industries, and opening up fresh sales channels. Steve Jobs, Jeff Bezos, Elon Musk, Sara Blakely, and Mark Zuckerberg are just a few examples of successful entrepreneurs who have transformed their respective sectors by a combination of consumer focus, technological innovation, resourcefulness, and resilience. This article provides a glimpse into the future of entrepreneurship and company strategy by highlighting rising themes. Key drivers of entrepreneurship are innovation enabled by technology, as well as sustainability, globalisation, collaboration, and adaptability. Entrepreneurs may generate good change, create value, and deal with the uncertainties of today’s difficult business climate by capitalising on these trends.